ANALISIS PERKEMBANGAN PENELITIAN KOMUNIKASI PEMASARAN DAN KONTEN DIGITAL - Heni Indrayani; Swita Amalia Hapsari; Hanif Wahyu Cahyaningtyas; Rifqi Hindami (Dialektika, 2019)
Students try to communicate scientifically through information written in their final project in the form of a Thesis. In the distribution of research topics in the Communication Studies program at Dian Nuswantoro University, most discussed digital content and marketing communication. Therefore, the purpose of this research is to analyze the development of digital content research and marketing communications. The method used is a descriptive quantitative method with a bibliometric approach from 21 thesis of Communication Studies Program students from August 2017 to March 2019. The results showed that the study of Communication Studies Program Students at Dian Nuswantoro University was the most adalagh of analyzing digital content and marketing communications. This is in accordance with specialization in the study program. Digital content both online media, social media and Youtube are discussed in terms of strategy and media platform content. Meanwhile, marketing communication research discusses the strategy side and impact of marketing communication.